2022
DOI: 10.1186/s12877-022-03203-3
|View full text |Cite
|
Sign up to set email alerts
|

Fasting blood glucose-to-glycated hemoglobin ratio and all-cause mortality among Chinese in-hospital patients with acute stroke: a 12-month follow-up study

Abstract: Background Stroke is a leading cause of death and functional impairment in older people. To assess the prospective association between fasting blood glucose-to-glycated hemoglobin ratio and all-cause mortality and poor prognosis in stroke patients. Methods A total of 971 Chinese inpatients with acute stroke (mean age of 65.7) were consecutively enrolled in the prospective clinical study and followed up for 12 months after discharge. Stress hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…30 Another prospective study indicated that a higher quartile of stress hyperglycemia was related to a higher risk of all-cause death after stroke. 31 T A B L E 2 Hazard ratios for stroke recurrence according to the glycemic gap. The potential mechanisms of the association between the glycemic gap and stroke recurrence might be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Another prospective study indicated that a higher quartile of stress hyperglycemia was related to a higher risk of all-cause death after stroke. 31 T A B L E 2 Hazard ratios for stroke recurrence according to the glycemic gap. The potential mechanisms of the association between the glycemic gap and stroke recurrence might be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al suggested that stress hyperglycemia was associated with poor functional outcome in patients with ischemic stroke 30 . Another prospective study indicated that a higher quartile of stress hyperglycemia was related to a higher risk of all‐cause death after stroke 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Both their study and ours suggest that higher fasting blood glucose is associated with an increased mortality risk in non-diabetic patients with ACI. Stress hyperglycaemia was measured by FBG/HbA1c ratio in a study by Cai et al 24 Their study showed that patients in the highest quartile of the FBG/HbA1c ratio had an increased risk of all-cause death at 3 months (OR: 5.16) and at 12 months (OR: 2.59) after stroke. In contrast, our results showed that the 3-month all-cause mortality in Q4 (>5.55 mmol/L) was significantly increased compared with Q1 (<4.52 mmol/L).…”
Section: Open Accessmentioning
confidence: 99%